The Protein Disulfide Isomerase of Botrytis cinerea: An ER Protein Involved in Protein Folding and Redox Homeostasis Influences NADPH Oxidase Signaling Processes - Marschall, Robert; Tudzynski, Paul (Frontiers in Microbiology, 2017)
Botrytis cinerea is a filamentous plant pathogen, which infects hundreds of plant species; within its lifestyle, the production of reactive oxygen species (ROS) and a balanced redox homeostasis are essential parameters. The pathogen is capable of coping with the plant’s oxidative burst and even produces its own ROS to enhance the plant’s oxidative burst. Highly conserved NADPH oxidase (Nox) complexes produce the reactive molecules. The membrane-associated complexes regulate a large variety of vegetative and pathogenic processes. Besides their commonly accepted function at the plasma membrane, recent studies reveal that Nox complexes are also active at the membrane of the endoplasmic reticulum. In this study, we identified the essential ER protein BcPdi1 as new interaction partner of the NoxA complex in B. cinerea. Mutants that lack this ER chaperone display overlapping phenotypes to mutants of the NoxA signaling pathway. The protein appears to be involved in all major developmental processes, such as the formation of sclerotia, conidial anastomosis tubes and infection cushions (IC’s) and is needed for full virulence. Moreover, expression analyses and reporter gene studies indicate that BcPdi1 affects the redox homeostasis and unfolded protein response (UPR)-related genes. Besides the close association between BcPdi1 and BcNoxA, interaction studies provide evidence that the ER protein might likewise be involved in Ca2+ regulated processes. Finally, we were able to show that the potential key functions of the protein BcPdi1 might be affected by its phosphorylation state.